Androgen production in women - Burger, Henry G (Fertility and sterility, 2002)
To describe the sources, production rates, circulating concentrations, and regulatory mechanisms of the major androgen precursors and androgens in women. Review of the major published literature. Quantitatively, women secrete greater amounts of androgen than of estrogen. The major circulating steroids generally classified as androgens include dehydroepiandrosterone sulphate (DHEAS), dehydroepiandrosterone (DHEA), androstenedione (A), testosterone (T), and dihydrotestosterone in descending order of serum concentration, though only the latter two bind the androgen receptor. The other three steroids are better considered as pro-androgens. Dehydroepiandrosterone is primarily an adrenal product, regulated by adrenocorticotropic hormone (ACTH) and acting as a precursor for the peripheral synthesis of more potent androgens. Dehydroepiandrosterone is produced by both the ovary and adrenal, as well as being derived from circulating DHEAS. Androstenedione and testosterone are products of the ovary and the adrenal. Testosterone circulates both in its free form, and bound to protein including albumin and sex steroid hormone-binding globulin (SHBG), the levels of which are an important determinant of free testosterone concentration. The postmenopausal ovary is an androgen-secreting organ and the levels of testosterone are not directly influenced by the menopausal transition or the occurrence of menopause. Dihydrotestosterone (DHT) is primarily a peripheral product of testosterone metabolism. Severe androgen deficiency occurs in hypopituitarism, but other causes may lead to androgen deficiency, including Addison's disease, corticosteroid therapy, chronic illness, estrogen replacement (leads to elevated SHBG and, therefore, low free testosterone), premenopausal ovarian failure, or oophorectomy.